Lantibiotics biosynthesis genes and bacteriocinogenic activity of Lactobacillus spp. isolated from raw milk and cheese - Perin, Luana Martins; Moraes, Paula Mendonça; Silva, Abelardo; Nero, Luís Augusto (Folia microbiologica, 2012)
Lactobacillus species are usually used as starters for the production of fermented products, and some strains are capable of producing antimicrobial substances, such as bacteriocins. Because these characteristics are highly desirable, research are continually being performed for novel Lactobacillus strains with bacteriocinogenic potential for use by food industries. The aim of this study was to characterise the bacteriocinogenic potential and activity of Lactobacillus isolates. From a lactic acid bacteria culture collection obtained from raw milk and cheese, 27 isolates were identified by 16S rDNA as Lactobacillus spp. and selected for the detection of lantibiotics biosynthesis genes, bacteriocin production, antimicrobial spectra, and ideal incubation conditions for bacteriocin production. Based on the obtained results, 21 isolates presented at least one of the three lantibiotics biosynthesis genes (lanB, lanC or lamM), and 23 isolates also produced antimicrobial substances with sensitivity to at least one proteinase, indicating their bacteriocinogenic activity. In general, the isolates had broad inhibitory activity, mainly against Listeria spp. and Staphylococcus spp. strains, and the best antimicrobial performance of the isolates occurred when they were cultivated at 25 °C for 24 or 48 h or at 35 °C for 12 h. The present study identified the bacteriocinogenic potential of Lactobacillus isolates obtained from raw milk and cheese, suggesting their potential use as biopreservatives in foods.
Keywords: mléko; Microbial Sensitivity Tests; DNA, Ribosomal; ribozomální DNA; RNA, Ribosomal, 16S; Bacteriocins; RNA ribozomální 16S; mikrobiální testy citlivosti; Anti-Bacterial Agents; Milk; Animals; biosyntetické dráhy; Lactobacillus; Sequence Analysis, DNA; zvířata; DNA bakterií; Biosynthetic Pathways; bakteriociny; DNA, Bacterial; sýr; sekvenční analýza DNA; antibakteriální látky; Cheese